Традиційне будівництво на Малинщині - Гудченко, З. (Народна творчість та етнографія, 2006)
The following article is the analysis of the settlements in Malynshchyna, Polissya. The author gives the information that contains written historical sources about the process of building in the region. A great attention is paid to oral sources — the records of the peasants' narrations. The author gives the information about the ethnic diversity of the region. The rituals connected with building are described brightly. The facts about wells as the element of settlements are suggested. At the end a description of a traditional house is depicted.